Multiple sclerosis in South America: month of birth in different latitudes does not seem to interfere with the prevalence or progression of the disease - Yara Dadalti Fragoso; Tarso Adoni; Sandra Maria Garcia de Almeida; Soniza Vieira Alves-Leon; Walter Oleschko Arruda; Fiorella Barbagelata-Aguero; Joseph Bruno Bidin Brooks; Adriana Carra; Rinaldo Claudino; Elizabeth Regina Comini-Frota; Eber Castro Correa; Alfredo Damasceno; et al. (Arquivos de Neuro-Psiquiatria)
Objective To assess whether the month of birth in different latitudes of South America might influence the presence or severity of multiple sclerosis (MS) later in life. Methods Neurologists in four South American countries working at MS units collected data on their patients' month of birth, gender, age, and disease progression. Results Analysis of data from 1207 MS patients and 1207 control subjects did not show any significant variation in the month of birth regarding the prevalence of MS in four latitude bands (0–10; 11–20; 21–30; and 31–40 degrees). There was no relationship between the month of birth and the severity of disease in each latitude band. Conclusion The results from this study show that MS patients born to mothers who were pregnant at different Southern latitudes do not follow the seasonal pattern observed at high Northern latitudes.